Actions of the TrkB Agonist Antibody ZEB85 in Regulating the Architecture and Synaptic Plasticity in Hippocampal Neurons - Tacke, Charlotte; DiStefano, Peter S.; Lindsay, Ronald M.; Metzdorf, Kristin; Zagrebelsky, Marta; Korte, Martin (Frontiers in Molecular Neuroscience, 2022)
Signaling of BDNF via its TrkB receptor is crucial in regulating several critical aspects of the architecture and function of neurons both during development and in the adult central nervous system. Indeed, several neurological conditions, such as neurodevelopmental and neurodegenerative disorders are associated with alterations both in the expression levels of BDNF and TrkB, and in their intracellular signaling. Thus, the possibility of promoting BDNF/TrkB signaling has become relevant as a potential therapeutic intervention for neurological disorders. However, the clinical potential of BDNF itself has been limited due to its restricted diffusion rate in biological tissue, poor bioavailability and pharmacological properties, as well as the potential for unwanted side effects due to its ability to also signal via the p75NTR pathway. Several small molecule and biologic drug candidate TrkB agonists have been developed and are reported to have effects in rescuing both the pathological alterations and disease related symptoms in mouse models of several neurological diseases. However, recent side-by-side comparative studies failed to show their specificity for activating TrkB signaling cascades, suggesting the need for the generation and validation of improved candidates. In the present study, we examine the ability of the novel, fully human TrkB agonist antibody ZEB85 to modulate the architecture, activity and synaptic plasticity of hippocampal murine neurons under physiological conditions. Moreover, we show here that ZEB85 prevents β-amyloid toxicity in cultured hippocampal neurons, in a manner which is comparable to BDNF.